Urban Environmental Health and Sensitive Populations: How Much Are the Italians Willing to Pay to Reduce Their Risks? - Anna Alberini; Aline Chiabai (European Regional Science Association (ERSA), 2006)
We use contingent valuation to elicit WTP for a reduction in the risk of dying for cardiovascular and respiratory causes, the most important causes of premature mortality associated with heat wave and air pollution, among the Italian public. The purpose of this study is three-fold. First, we obtain WTP and VSL figures that can be applied when estimating the benefits of heat advisories, other policies that reduce the mortality effects of extreme heat, and environmental policies that reduce the risk of dying for cardiovascular and respiratory causes. Second, our experimental study design allows us to examine the sensitivity of WTP to the size of the risk reduction. Third, we examine whether the WTP of populations that are especially sensitive to extreme heat and air pollution—such as the elderly, those in compromised health, and those living alone and/or physically impaired—is different from that of other individuals. We find that WTP, and hence the VSL, depends on the risk reduction, respondent age (via the baseline risk), and respondent health status. WTP increases with the size of the risk reduction, but is not strictly proportional to it. All else the same, older individuals are willing to pay less for a given risk reduction than younger individuals of comparable characteristics. Poor health, however, tends to raise WTP, so that the appropriate VSL of elderly individuals in poor health may be quite large. Our results support the notion that the VSL is "individuated."
Keywords: 330